(3GdOhQ GdJQHhj ddJdaRjhf hGdGfJQfJ (B( (3fehPL efWbI WQGHdS (B- (3GdTeGd (B)s - (3HjJjI , YHjQ CMeOs ((3HjQhJs (3GdLGeYI GddHfGfjI (B- (3eYgO GdYdhe GdGLJeGYjIs, 2004)
(3JgOa GdOQGSI Edi JHjGf MbjbI eG jfSH Edi GdJdaRjhf hGdEfJQfJ hOhQgeG hJCKjQgeG aj GdYedjI GdJQHhjI, hJCKQ GdeQGgb HJdc GdKbGaGJ hGdeYGQa hGdWQb GdJQHhjI, heG ehbYg ef GdYdGbI HGdUhQI hGdTGTI hJMOjOkG HGdJdaRjhf hGdEfJQfJ, hcja JDKQ gPg GdYdGbI aj HfGFg GdKbGaj hGdJQHhj hgd jSYi Edi GbJHGS cd eG gh LOjO hjfWdb HGdKbGaGJ GdCNQi Ohf hYj hEOQGc hGdJejjR Hjf eG gh fGaY hVGQ(B. (3EYJeOJ GdOQGSI GdefgL GdhKGFbj hefgL GdeSM HGdYjfI deFI eQGgb JJQGhM CYeGQge Hjf (B13 (3h (B17 (3SfI,ef GdUaha GdeJhSWI hGdKGfhjI aj eOGQS NGUI hQSejI OGNd eOjfI WQGHdS fUage EfGK hfUage PchQ ef eNJda GdeSJhjGJ GdGLJeGYjI(B. (3hGSJNOeJ JbfjI GdebGHdI, GdedGMXI, JMdjd GdeVehf, hGdGSJeGQI dLeY GdeYdheGJ(B. (3JHjf GdfJGFL Cf GdJdaRjhf hGdEfJQfJ jSJCKQGf chSGFd ddJSdjI, GdJQajg, hGdJKbja HMUI cHjQI ef GdhbJ dOi GdeQGgbjf, aejdge dgPG GdfhY ef GdTGTGJ CcKQ ef ejdge Edi GdeWGdYI, ceG JaQV JbfjGJ GdGJUGd (B((3GdJdaRjhf hGdEfJQfJ(B) (3KbGaJgG Ydi GdeQGgbjf, hQHeG bO JDKQ SdHG Ydi KbGaJge hJQHjJge hYGOGJge Ohf Cf jSJWjY GdeQGgb CNP eG gh LjO hJQc eG gh VGQ, ceG jJe GSJYeGd GdTHcI HCgOGa eJYOOI efgG eG jchf HYjkOG Yf GdeLGd GdJQHhj hGdJYdjej(B. (3JHjf CjVG Cf JYdb GdeQGgbjf HGdJdaRjhf hGdEfJQfJ Edi OQLI cHjQI, heTGgOI CfhGY ef GdbfhGJ jDKQ Ydi feW hSdhc heaGgje hJQHjI GdeQGgb(B. (3hbO jDKQ Ydi fTGWge GdGLJeGYj hjTLYge Ydi GdGfYRGd Yf eMjWge GdLZQGaj, agfGc JhLg ef bHd WdGH GdeOGQS GdNGUI hWdGH GdeQMdI GdKGfhjI fMh GdEfJQfJ CcKQ ef WdGH GdeOGQS GdQSejI hGdeQMdI GdeJhSWI(B.s
(3GdfhY (B: (3QSGdIs
Keywords: Education et la technologie; ICT and Education; (3GdJYdje hGdJcfhdhLjGs; (3WQGHdSs